2006
DOI: 10.1140/epjb/e2006-00399-x
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics of an irreversible thermally driven Brownian microscopic heat engine

Abstract: We model a Brownian heat engine as a Brownian particle that hops in a periodic ratchet potential where the ratchet potential is coupled with a linearly decreasing background temperature. It is shown that the efficiency of such Brownian heat engine is far from Carnot efficiency even at quaistatic limit. At quasistatic limit, the efficiency of the heat engine approaches the efficiency of endoreversible engine η = 1 − Tc/T h [23]. On the other hand, the maximum power efficiency of the engine approaches η M AX = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…Similarly, other expressions for efficiency at maximum power, such as in irreversible models of stochastic engines [40][41][42], which obey a different universality near equilibrium, can also be reproduced from the inference based approach [32,43]. Thus, the latter approach provides an effective way of analyzing the performance of energy conversion systems.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, other expressions for efficiency at maximum power, such as in irreversible models of stochastic engines [40][41][42], which obey a different universality near equilibrium, can also be reproduced from the inference based approach [32,43]. Thus, the latter approach provides an effective way of analyzing the performance of energy conversion systems.…”
Section: Introductionmentioning
confidence: 97%
“…This may indicate that the general case of prior ignorance about two parameters may belong to a different universality class than the special case of ignorance about a single parameter, which is bounded from below by half Carnot value [10,11]. Further, we note that in a model of irreversible Brownian heat engine [12], when the power is optimised with respect to the load and the barrier height, the efficiency at optimal power is found to be given by…”
Section: Discussionmentioning
confidence: 95%
“…Recently, the study of microscopic heat engines rectifying thermal fluctuations has attracted considerable attention [1][2][3][4][5][6][7][8], including Brownian heat engines, stochastic heat engines, diode engines, and so on. One typical model of the microscopic engines rectifying thermal fluctuations is Feynman's ratchet and pawl engine [9][10][11]. Feynman et al [9] attempted to investigate the thermodynamics of the Feynman-Smoluchowski (FS) motor and concluded that it can reach Carnot efficiency.…”
Section: Introductionmentioning
confidence: 99%